(untitled) (Medical Forum Monthly, 2024)
Objective: To observe the frequency and Fetomaternal outcome of pregnancies with acute appendicitis. Study Design: Prospective / observational study Place and Duration of Study: This study was conducted in gynecology and surgical department of Ghulam Muhammad Mahar Medical College Teaching Hospital Khairpur Sindh from January 2010 to December 2012. Materials and Methods: All pregnant ladies admitted in Gynae and surgical department with history of acute pain in abdomen and strong suspicious of acute appendicitis on the basis of history, clinical examination and ultrasound findings after exclusion of other gynecological and surgical causes of acute abdomen during pregnancy were included in the study for following variables: Presentation, duration of symptoms, operative findings and complications associated with disease and operative procedure were noted. Data was collected on pre-designed Performa and analyzed on SPSS version 15. Results: During 3 year study period total 8700 Obstetric admission and cases with strong suspicious of acute appendicitis in pregnancy was 20 (0.22%), most women belongs to age between 18-40 years. More cases seen 2nd trimester 11(55%), duration of symptoms < 24 hours seen in 85% and >24 hours seen in 15% of cases. Abdominal pain was leading symptom present in 80% of cases while lower abdominal tenderness was leading sign seen in 90%. On surgery signs of acute appendicitis seen in 75%, normal looking appendix in 10%, while perforated appendix with moderate pus in peritoneal cavity seen in 15% of cases. One maternal death was seen in study population due to septicemia, most probably because of late presentation. Conclusion: The evaluation of a pregnant woman presenting with acute abdominal pain warrants a careful workup due to the possible risks for the fetus and mother if appendix perforates.